The Contributions of Traditional Architecture to Sense of Place: a Study of the Traditional Hotels of Fremantle - Ali, Shaymaa Abbas (Curtin University, 2019)
This research examines the role played by hotels located in historic areas in stimulating a sense of place for community members. More specifically, this research focuses on how the formal characteristics of ‘traditional hotels’ impact a local community’s understandings and emotions in regard to place. Fremantle’s West End and its traditional hotels are utilised as a case study, and the research framework draws on Henri Lefebvre’s space triad to help achieve the research objectives.